Association of functional nucleotide polymorphisms at DTH2 with the northward expansion of rice cultivation in Asia - Wu, Weixun (National Academy of Sciences, 2013)
Flowering time (i.e., heading date in crops) is an important ecological trait that determines growing seasons and regional adaptability of plants to specific natural environments. Rice (Oryza sativa L.) is a short-day plant that originated in the tropics. Increasing evidence suggests that the northward expansion of cultivated rice was accompanied by human selection of the heading date under noninductive long-day (LD) conditions. We report here the molecular cloning and characterization of DTH2 (for Days to heading on chromosome 2), a minor-effect quantitative trait locus that promotes heading under LD conditions. We show that DTH2 encodes a CONSTANS-like protein that promotes heading by inducing the florigen genes Heading date 3a and RICE FLOWERING LOCUS T 1, and it acts independently of the known floral integrators Heading date 1 and Early heading date 1. Moreover, association analysis and transgenic experiments identified two functional nucleotide polymorphisms in DTH2 that correlated with early heading and increased reproductive fitness under natural LD conditions in northern Asia. Our combined population genetics and network analyses suggest that DTH2 likely represents a target of human selection for adaptation to LD conditions during rice domestication and/or improvement, demonstrating an important role of minor-effect quantitative trait loci in crop adaptation and breeding.